Monitoring and Modelling Morphological Changes in Rivers Using RS and GIS Techniques - Zainab Dekan Abbass; Jaafar S. Maatooq; Mustafa M. Al-Mukhtar (Civil Engineering Journal, 2023)
River geomorphological investigation issues have received little attention in most countries of the world. Such processes become a pressing necessity due to climate change and anticipated events of extraordinary surges and dry seasons, which may debilitate the security of adjacent and downstream cities, particularly in locales that are exceedingly delicate and influenced by climatic changes. Al-Abbasia reach is a river that runs through the middle of the Euphrates River and is known for its numerous bends and meanders. The study of hydraulic structures such as barrages can provide important information about their influences on morphological processes in river reaches near the barrage upstream and downstream. Hydraulic analysis is made of the river behavior in u/s and d/s of hydraulic structures like barrages as a result of sediment deposition and erosion in u/s and d/s. A study, i.e., research on the impacts of the Abbassia barrage on the river system, has been conducted to address this issue using multi-temporal Landsat satellite data from 1976 to 2022 provided by the USGS. The study reach is located 5 kilometres upstream and 5 kilometres downstream of the Abbassia reach. Following the construction of the barrage, which had an impact on the sedimentation and geometry of the river, morphological variations took place in this part of the Al Abbassia reach. In this study, morphological changes throughout 49 years between 1976 and 2022 were investigated utilising remote sensing (RS) and geographic information system (GIS) approaches. Additionally, four image groups from three separate decades were used to perform change detection (1990–2000, 2000–2010, and 2010–2022). In this study, a monitoring system using Landsat-3 MSS: 1985, Landsat-5 TM: 1990, 1995, 2000, 2005, and Landsat-8 OLI: 2010, 2011, 2015, 2021, 2022 were employed to map river planform changes. The long-term comparison of this series of satellite images and historical maps for the period 1976–2022 indicates a continuation of change in the reach study with a rate of approximately 56, 33, 97, and 55% for upstream and 19%, 26%, 3%, and 45% for downstream for the width, area, deposition, and erosion, respectively. Furthermore, it is observed that there is a shift in river course within 200 m downstream of the barrage for the period of 1985–1990. The findings of this study, which monitor river morphological change at finer temporal and spatial resolutions, are crucial for promoting sustainable river management. They also aid in the investigation of river behaviour, which is necessary for providing the best management possible and overcoming the difficulties posed by this important research issue. Doi: 10.28991/CEJ-2023-09-03-03 Full Text: PDF